2017
DOI: 10.1016/j.jmrt.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and ionic conductivity studies on microwave synthesized glasses containing transition metal ions

Abstract: Please cite this article in press as: Sujatha B, et al. Electronic and ionic conductivity studies on microwave synthesized glasses containing transition metal ions. J Mater Res Technol. 2016. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…On the other hand, glasses which exhibit significant contribution of polaronic conduction along with the ionic one show two semicircles in the impedance plot, Figure 5B. 22,[29][30][31][32][33] In our study we applied gold electrodes for electrical measurements which are blocking for ions and non-blocking for polarons. 22,[29][30][31][32][33] In our study we applied gold electrodes for electrical measurements which are blocking for ions and non-blocking for polarons.…”
Section: Electrical Transportmentioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, glasses which exhibit significant contribution of polaronic conduction along with the ionic one show two semicircles in the impedance plot, Figure 5B. 22,[29][30][31][32][33] In our study we applied gold electrodes for electrical measurements which are blocking for ions and non-blocking for polarons. 22,[29][30][31][32][33] In our study we applied gold electrodes for electrical measurements which are blocking for ions and non-blocking for polarons.…”
Section: Electrical Transportmentioning
confidence: 91%
“…Four series of glasses in the quaternary systems: 10,20,30,40,50, 60 (mol%) B) xWO 3 -(30À0.5x)Na 2 O-(30À0.5x)ZnO-40P 2 O 5 , with x = 0, 10, 20, 30, 40, 50, 60 (mol%) 10,20,30,40,50, 60 (mol%) 10, 20, 30, 40, 50, 60 (mol%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multicomponent glasses containing TMO (V 2 O 5 , Fe 2 O 3 , CuO, MoO 3 , WO 3 , etc), glass former (B 2 O 3 , P 2 O 5 , TeO 2 , etc), and alkali oxides as modifiers (Li 2 O, Na 2 O, etc) have been extensively reviewed . These glasses are known to be mixed ionic‐electronic conductors .…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent glasses containing TMO (V 2 O 5 , Fe 2 O 3 , CuO, MoO 3 , WO 3 , etc), glass former (B 2 O 3 , P 2 O 5 , TeO 2 , etc), and alkali oxides as modifiers (Li 2 O, Na 2 O, etc) have been extensively reviewed. [9][10][11][12] These glasses are known to be mixed ionic-electronic conductors. 10,11 It was found that alkali-free oxide glasses 13,14 in the TeO 2 -V 2 O 5 -MoO 3 and V 2 O 5 -Sb-TeO 2 systems 15 have nonohmic conduction leading to negative resistance/switching phenomenon at high electric fields.…”
Section: Introductionmentioning
confidence: 99%